Virtual Meeting Technology Adoption for Business Management in Small and Medium-Sized Enterprises - Suhardi, Hardi; Simon, Iman Ulung; Tamara, Dewi; Furinto, Asnan (International Journal of Supply Chain Management, 2020)
Abstract Purpose – The objective of this paper is to study the impact of virtual meeting technology adoption towards the productivity of employees in Jakarta during COVID-19 pandemic. Design/methodology/approach – The authors conducted a descriptive research using questionnaires distributed to employees in Jakarta. Findings – The study has found that the adoption of virtual meeting technology has had significant and positive impact to the productivity of employees in Jakarta during COVID-19 pandemic. The impact on productivity is partially mediated or influenced by employees’ satisfaction while using the technology. Research limitations/implications – The technology impact to non-employees such as entrepreneurs and freelance workers are not within the scope of this study, as well as employees working outside Jakarta. Practical implications – The findings of this study help provide insight for companies in Jakarta to emphasize more on the adoption of virtual meeting technology as well as providing the necessary support for employees to use the technology in the best ways. Originality/value – Little research has been done to study the impact of virtual meeting technology towards employees’ productivity. And it is even less done in Jakarta especially during COVID-19 pandemic.